Association of Employees Orientation of Customers and Their Satisfaction in Departmental Stores Around Jaipur City - MADHAVI, THAYA; MEHROTRA, RAJESH (The journal of contemporary issues in business and government, 2021)
A review of study provided by operational level employees is more often depended on their attitude towards customers while dealing with any item of product to be disposed of or sold to the customer. That would obviously speak on the quality of service being provided to the customer. This would remain an important factor to confer sufficient amount of leverage for the success of an organization. This paper particularly emphasize on the static relationship maintained between customer orientation and customer satisfaction on the part of departmental stores employees. A survey has been conducted on 100 employees through questionnaire mode. The results have predicted positive correlationship between customer satisfaction and customer orientation. This might ultimately lead to retention and customer commitment in the business front.